Computational Screening And In Vitro Study Of Malaysian Plants For Anti Obesity Properties Targeting Pancreatic Lipase - Husain, Nurul Nasuha (2019)
Pancreatic lipase is the enzyme responsible for hydrolysis of dietary fats to free fatty acids and monoacylglycerol. High intake of dietary fats will cause excess accumulation of fat in the body and will further cause overweight and obesity. In order to find alternatives for anti-obesity agents, in silico screening and in vitro methods were employed, targeting pancreatic lipase to restrain hydrolysis of dietary fat. In silico screening was first done using 3963 phytochemical compounds from NADI database, which were docked onto pancreatic lipase (PDB ID: 1LPB). From the screening results, 13 plants with top hits compounds were identified namely, Momordica charantia, Jatropha curcas, Endiandra kingiana, Calophyllum inophyllum, Garcinia mangostana, Chisocheton ceramicus, Aglaia argentea, Artocarpus champeden, Manilkara zapota, Dysoxylum hainanense, Capsicum annum, Oryza sativa and Hopea hainanensis. The crude methanolic extracts of these selected plants were tested for in vitro study to investigate inhibition activity against pancreatic lipase. From in vitro assessment, the methanolic extract of Manilkara zapota was recognized as potential inhibitor for pancreatic lipase with 92.5 % inhibition, followed by Oryza sativa (77.7 %), Garcinia mangostana (60 %), Endiandra kingiana (58 %) and Momordica charantia (13.3 %). Docking assessment of Manilkara zapota was evaluated to discover the predicted compounds with anti lipase properties are from terpene group.